Labour Market Diversification through Digital and Sustainable Work - Fryczyńska, Marzena; Skrzek-Lubasińska, Małgorzata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The aim of this article is to examine the diversification of the labour market in Poland based on sustainability and digitalisation of work in the context of remote jobs.Research Design & Methods: The study employs a quantitative methodology, to analyse data from 1,035 workers whose jobs can be performed remotely (outside the company’s premises, using modern technologies) with ICT support.Findings: The study identified four distinct cohorts representing varying levels of digital and sustainable work. Results show significant differences in demographic and employment characteristics, with income, sector, and working hours influencing digitalisation and sustainability. The findings highlight the uneven distribution of digital and sustainable work across the labour market, emphasising the need for targeted strategies to bridge these gaps.Implications / Recommendations: The study concludes with recommendations for expanding digitalisation opportunities and implementing tailored practices to boost work sustainability. This research underscores the need for strategic considerations and further research in this evolving field.Contribution: This research contributes to the understanding of the complex relationship between digitalisation and work sustainability. It provides valuable insights into labour market diversification and offers practical recommendations for enhancing work sustainability in the digital age. The findings of this study have implications for policymakers, employers, and workers navigating the evolving digital landscape.